Verification of formaldehyde emission testing by desiccator method / Rafeadah R. …[et al.] - R., Rafeadah; S., Rahim; Koh., M.P.; M., Suffian; M., Habibah; A., Azlina (2006)
The objective of this study was to investigate the effect of conditioning duration and desiccator environment on formaldehyde emission by desiccator method (JIS A 1460: 2001). The medium density fibreboard (MDF) sample was obtained from the manufacturer and cut into standard size required of 50 mm x 150 mm for conditioning and testing purposes. For the duration of conditioning, samples were taken out for every 1, 3 and 7 days for formaldehyde content analysis. These desiccators were placed at two locations: growth chamber (temperature controlled at 20 ± 0.5°C) and normal room condition. The results show that the amount of formaldehyde released from the samples was steadily decreased as the duration of conditioning increased from 1 to 7 days for both growth chamber and normal room conditions. The formaldehyde content for samples located in growth chamber generally lower than the samples conditioned at room temperature.